Analysis of thermal processes occurring in heated multilayered metal films using the dual-phase lag model - Majchrzak, E.; Kałuża, G. (Archives of Mechanics, 2017)
A multilayered thin metal film subjected to an ultra-short laser pulse is considered. A mathematical description of the discussed process is based on the system of the dual-phase lag equations supplemented by appropriate boundary and initial conditions. Special attention is devoted to the ideal contact conditions at the interfaces between the layers, which in the case of the dual-phase lag model must be formulated in a different way than in the macroscopic Fourier model. To solve the problem the explicit scheme of the finite difference method is developed. In the final part of the paper the example of computations is shown.